N-Heterocyclic Carbene-Catalyzed Enantioselective Annulations: A Dual Activation Strategy for a Formal [4+2] Addition for Dihydrocoumarins - Lee, Anna (Chem Commun (Camb), 2015)
A highly efficient asymmetric formal [4+2] annulation for the synthesis of dihydrocoumarins has been developed via an in situ activated NHC catalysis. Both electrophilic and nucleophilic species are generated in situ simultaneously whereby acyl imidazoles facilitated rapid formation of an NHC-enolate intermediate to afford the [4+2] dihydrocoumarin adducts.